Startle habituation: a tool for assessing information processing deficits in zebrafish model of schizophrenia - Png, Wen-Yang; Tang, Pek-Yee; Ogawa, Satoshi; Parhar, Ishwar; Mok, Siew-Ying (Penerbit Universiti Kebangsaan Malaysia, 2021)
Prepulse inhibition (PPI) and habituation of acoustic startle reflex have been extensively used to assess deficits in the sensorimotor functions of human patients and animal models of schizophrenia. These assays require expensive and sophisticated experimental setup for fine control of acoustic stimuli and sound attenuation. In this study, we investigate whether startle habituation assay based on mechanical (tap) stimuli can induce similar impairment in the habituation response in the schizophrenia model of larval zebrafish. For this purpose, a custom startle apparatus consisting of a 9 V push and pull solenoid and an Arduino Uno microcontroller was used to generate tap stimuli at desired intervals. Our results showed that tap stimuli at 1 Hz effectively evoked startle response in the control fishes which habituated after a few trials. The habituation response was significantly impaired in the MK801-induced schizophrenia model, similar to that elicited by acoustic startle stimuli in a previous study. We propose this simple and inexpensive method as an alternative tool for studying information processing and attention deficits in the pharmacological model of schizophrenia in zebrafish.